PENCAPAIAN INDIKATOR PRIORITAS TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGS) YANG BERSUMBER DARI SUSENAS DI KABUPATEN MANGGARAI 2015-2023 - Muhamad Andriansyah; Devi Daria; Maria Septiani Gabur (Jurnal Statistika Terapan (ISSN 2807-6214), 2024)
The time for completion of the Sustainable Development Goals agreement will soon be nearing its end in 2030. In the remaining time, it is the government's duty to make movements to achieve the predetermined targets. It all starts with data. Good data management will make evaluation and development planning right on target, effective and efficient. Likewise, its application to SDGs indicator data is both at the central and regional levels. SDGs indicators sourced from National Socio-Economic Survey (Susenas) activities are 39 out of 289 indicators in total, of which 17 Susenas indicators are priority indicators. This research focuses on the achievements of SDGs priority indicators sourced from Susenas and indicators analyzed in the SDGS Road Map document in Manggarai Regency. The results obtained show that the achievement of indicators in Manggarai Regency is still on the right track, although several indicators require the government to intervene more to resolve them.